Regional Intravenous Anaesthesia (Bier’s block) in Black-headed Vulture (Coragyps atratus) Submitted to Digit Amputation - Demczuk Thomas, Lettycia; Piccoli, Ronaldo José; Sinotti, Jéssica Fernanda; Fucks de Souza, Carolina; Bono Fukushima, Fabiola (Acta Scientiae Veterinariae, 2022)
Background: The Coragyps atratus flies long distances in search of food and has a marked behaviour of food competition. Since they are frequently found in areas of recent human occupation, they are subject to trauma, which may require surgical interventions. Locoregional blocks are used as part of a balanced-anaesthesia protocol and are currently being evaluated in birds, with brachial plexus block being the main technique described in the literature. However, to our knowledge, this is the first description of intravenous regional anaesthesia (Bier’s block) in a vulture. Thus, we aim to report the use of Bier’s block with 1% lidocaine, in a black-headed vulture submitted to digit amputation. Case: A black-headed vulture (Coragyps atratus), weighing 2 kg, was rescued and referred to the Veterinary Hospital due to its inability to fly. Physical examination revealed a swollen digit in the right pelvic limb. Radiographic examination confirmed the intermediate phalanx fracture of the 4th digit of the right pelvic limb with signs suggestive of advanced osteomyelitis. The animal was referred to surgery for amputation of the affected digit. Before surgery, water and food were withdrawn for 12 h. Pre-anaesthetic medication consisted of 1 mg/kg midazolam and 0.5 mg/kg morphine intramuscularly (IM). Anaesthetic induction was performed through face mask with isoflurane, followed by orotracheal intubation with a 3 mm-endotracheal tube. Anaesthesia was maintained with isoflurane through a non-rebreathing circuit in 100% oxygen. Using a multiparametric monitor, heart rate (HR), respiratory rate (RR), end-tidal CO2 (EtCO2), oxyhemoglobin saturation (SpO2), electrocardiography (ECG), systolic blood pressure (SBP) and core temperature (CT) were evaluated. Antisepsis of the right pelvic limb was performed and an elastic band was applied around the distal region of the affected tibia to serve as a tourniquet. A scalp vein set was used to access the lateral saphenous vein in the region distal to the tourniquet, and 5 mg/kg lidocaine 1% was injected intravenously. The patient remained stable during the procedure, with no need for analgesic rescue. The tourniquet was gradually released 40 min past its application, being completely removed after 45 min of surgery. The anaesthetic supply was interrupted, with extubation after 4 min; the patient had satisfactory anaesthetic recovery. Discussion: The present report describes the success in using the technique of intravenous regional anaesthesia with 1% lidocaine for digit amputation performed on a specimen of black-headed vulture. The pre-anaesthetic medication provided analgesia, satisfactory sedation for venoclysis, and anaesthetic induction without complications. Anaesthetic induction and maintenance in birds are preferably performed with inhaled anaesthetics, thus the choice of mask induction. Despite the reduction in RR soon after induction, the patient remained on spontaneous ventilation. Bier’s block using 5 mg/kg lidocaine showed to be an easy and safe technique in vultures, but doses up to 6 mg/kg lidocaine are not associated with adverse effects in birds. The intravenous regional anaesthesia technique described in this manuscript promoted adequate analgesia for the digit amputation procedure in black-headed vultures and allowed hemodynamic stability without significant anaesthetic complications. Thus, the present report points to the potential use of this locoregional block in other birds. Keywords: locorregional block, lidocaine, anaesthesia. Título: Anestesia regional intravenosa (bloqueio bier) em urubu-de-cabeça-preta (Coragyps atratus) submetido à amputação de dígito. Descritores: bloqueio locorregional, lidocaína, anestesia.